Study insights in the role of PGC-1α in neurological diseases: mechanisms and therapeutic potential - Tang, Mi-bo; Liu, Yi-xuan; Hu, Zheng-wei; Luo, Hai-yang; Zhang, Shuo; Shi, Chang-he; Xu, Yu-ming (Frontiers in Aging Neuroscience, 2025)
Peroxisome proliferator-activated receptor-γ coactivator-1α (PGC-1α), which is highly expressed in the central nervous system, is known to be involved in the regulation of mitochondrial biosynthesis, metabolic regulation, neuroinflammation, autophagy, and oxidative stress. This knowledge indicates a potential role of PGC-1α in a wide range of functions associated with neurological diseases. There is emerging evidence indicating a protective role of PGC-1α in the pathogenesis of several neurological diseases. As such, a deeper and broader understanding of PGC-1α and its role in neurological diseases is urgently needed. The present review provides a relatively complete overview of the current knowledge on PGC-1α, including its functions in different types of neurons, basic structural characteristics, and its interacting transcription factors. Furthermore, we present the role of PGC-1α in the pathogenesis of various neurological diseases, such as intracerebral hemorrhage, ischemic stroke, Alzheimer’s disease, Parkinson’s disease, Amyotrophic lateral sclerosis, Huntington’s disease, and other PolyQ diseases. Importantly, we discuss some compounds or drug-targeting strategies that have been studied to ameliorate the pathology of these neurological diseases and introduce the possible mechanistic pathways. Based on the available studies, we propose that targeting PGC-1α could serve as a promising novel therapeutic strategy for one or more neurological diseases.